Membaca Visi Ilmu dan Teknologi Kontemporer dari Sudut Pandang Filsafat Islam: Suatu Kemungkinan Elaborasi Awal berdasar Pendekatan Irfani - Ahmad Ibrahim Badry (Sekolah Tinggi Agama Islam Sadra, 2021)
This paper is a philosophical reflection on how the development of science and technology can be studied better through the tradition of Islamic philosophy. This is attempted because the approach that has been used to study science and technology in the Islamic world is still centered on the process of assimilation or Islamization of Knowledge. In a critical reading of the two approaches, the problems that arise from the study of contemporary science and technology become something that is difficult to anticipate. In fact, the development of science and technology is also moving very fast. This raises the question of the need for alternative approaches in the study of contemporary science and technology in the arena of Islamic Philosophy. To solve this problem, the author conducted an initial experiment that could elaborate ‘irfāniyyah's approach on the one hand with studies of contemporary science and technology on the other. This becomes possible with the reinterpretation of the concept of emanation that exists in the discourse of Yazdiyyah's ḥuḍūrī science. Based on this interpretation as well as the perspective that Miṣbāh Yazdi has made about the help of ‘irfān in philosophy, the application of the ‘irfāniyyah approach in the study of science and technology becomes possible as part of the practice of ḥuḍūrī science. On a more practical level, the author also uses this ‘irfāniyyah approach in a scenario format to read the vision of contemporary science and technology in the NBIC discourse.